Theoretical characterization of hexagonal 2D Be3N2 monolayers. (22nd January 2019) - Ullah, Saif; Denis, Pablo A.; Capaz, Rodrigo B.; Sato, Fernando
Abstract : With the help of DFT calculations, a possible synthesis method for monolayer Be3 N2 is proposed. Furthermore, its excellent thermal, dynamical, and mechanical stability makes it a material of comparable caliber to that of graphene. Abstract : First-principles density functional theory (DFT) calculations are performed to assess the stability, and geometric, mechanical, optical and electronic properties of monolayer graphene-like Be3 N2 . We find that Be3 N2 is a large band gap semiconductor with small electron and hole effective masses, which may promote its use in nanoelectronic devices. Furthermore, its excellent thermal, dynamical, and mechanical stability makes it a material of comparable caliber to that of graphene. In addition, the excellent electrochemical properties of Be3 N2 make it a unique material with possible theoretical capacities of 974 mA h g −1 for Li, Na, and K. Moreover, Be3 N2 can form bulk graphite-like layered structures with two different configurations, i.e. N2–N1 and N2–Be1. Finally, the derivatives of Be3 N2 (Be3 N2 nanoribbons) also possess direct band gaps which can be finely tuned to the desired level by geometry and morphology constraints. Based on these fascinating properties, Be3 N2 and its derivatives can find a broad range of applications in nanoelectronics and battery technologies.